STUDI TATA RUANG RUMAH TINGGAL SUKU TALANG MAMAK (Spatial Study Talang Mamak Tribe House) - Faisal, Gun; Wihardyanto, Dimas (Tesa Arsitektur, 2014)
The Talang Mamak tribe, one of Indonesian tribe, still practices the hunting and gathering of natural produce despite the fact that among them have chosen to settle permanently and doing farming activities. The aim of this research is to study the characteristics of the Talang Mamak house. The method used in this research is grounded theory method, based on the open coding, axial coding as well selective coding techniques. The method used to find the variation layout of the houses and then evaluate the characters and concept of the layouts. The conclusion of this study is that the core of the Talang Mamak house is based on the connectivity of four rooms namely: Ruang Haluan, Ruang Tangah, Ruang Tampuan and Pandapuran. The house has an open layout where all daily household activities are done without barriers. The social status of the owner is identified by houseâs furniture and staf